Sensorial and Nutritional Aspects of Cultured Meat in Comparison to Traditional Meat: Much to Be Inferred - Fraeye, Ilse; Kratka, Marie; Vandenburgh, Herman; Thorrez, Lieven (Frontiers in Nutrition, 2020)
Cultured meat aspires to be biologically equivalent to traditional meat. If cultured meat is to be consumed, sensorial (texture, color, flavor) and nutritional characteristics are of utmost importance. This paper compares cultured meat to traditional meat from a tissue engineering and meat technological point of view, focusing on several molecular, technological and sensorial attributes. We outline the challenges and future steps to be taken for cultured meat to mimic traditional meat as closely as possible.